A process evaluation of the walking in ScHools (WISH) study using the RE-AIM framework - Angela Carlin; Leanne C. Doherty; S. Maria O’Kane; Russell Jago; Ian M. Lahart; Gary McDermott; Maria Faulkner; Alison M. Gallagher; Marie H. Murphy (BMC Public Health, 2025)
Abstract Background Physical inactivity in adolescents is a major public health issue. Schools are important settings for physical activity interventions. The WISH Study was a peer-led, school-based walking intervention that aimed to increase physical activity levels of adolescent girls. This study uses the RE-AIM Framework to present the process evaluation of the WISH Study with a focus on factors that affected participation, motivation, and enjoyment of the intervention. Methods Pupils (n589 12–14 years) were recruited from 18 schools in the border region of Ireland and Northern Ireland. In intervention schools (n9), older pupils (15–18 years) were trained as walk leaders and led pupils (12–14 years) in brisk walks (10–15 min) during the school day, across the school year (2021-22). Questionnaires to measure self-efficacy for walking and physical activity, health-related quality of life and reasons for engaging in physical activity were administered throughout the intervention. At the end of the intervention focus groups were held with pupils, and interviews conducted with teachers and walk leaders. Attendance at walks was monitored by walk leaders. Quantitative data were analysed descriptively, and qualitative analysis was undertaken using thematic analysis. Themes were reported under RE-AIM indicators (reach, effectiveness, adoption, implementation, and maintenance). Results Pupils in the intervention schools (n286) were representative of adolescent girls in Northern Ireland and Ireland, in terms of their activity level. At baseline, 15% of these pupils met the recommended physical activity guidelines of 60 min moderate-vigorous physical activity per day, as measured by accelerometers. The total number of walks reported per school ranged from 2 to 104 across intervention schools. One quarter of pupils (n74, 26%) never attended a walk and 15% (n23) of walk leaders did not lead a walk. Pupils and walk leaders self-reported improvements in their physical health, mental well-being, and social relationships, and walk leaders reported gaining transferrable skills. Implementation was aided by school support in some schools, although barriers such as COVID-19, lack of time, harsh weather, inadequate facilities for indoor walks, and walk leader availability, were identified. Staff engagement was a key driver for the maintenance of walks. Conclusions Despite a promising feasibility study and a comprehensive walk leader training programme, the extent to which the intervention was adopted and implemented varied, suggesting future school-based physical activity interventions need to consider individual school contexts to ensure intervention fidelity. Trial registration ISRCTN 12847782